2008
DOI: 10.1142/s0217979208039897
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Rapid Solidification of Aluminum Under Pressure

Abstract: Molecular dynamics simulation study based on the EAM potential is carried out to investigate the effect of pressure on the rapid solidification of Aluminum. The radial distribution function is used to characterize the structure of the Al solidified under different pressures. It is indicated that a high pressure leads to strong crystallization tendency during cooling.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, application of high pressure during the cooling process will also be tested because high pressure leads to a strong tendency of crystallisation [20].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, application of high pressure during the cooling process will also be tested because high pressure leads to a strong tendency of crystallisation [20].…”
Section: Resultsmentioning
confidence: 99%
“…It mainly used in molecular dynamics related to some calculation and simulation work, generally speaking, relates to the field of molecular dynamics. Recently, there are a lot of researches to the metal material by MD, they have led to great progress, it is found that the slower cooling rate and increase the pressure is advantageous to the crystallization, such as Li [7], some papers consider that higher pressure to reinforce the crystallization trend, such as SARKAR [8]. But the microstructure variation study of Ni-Al alloy is scanty.…”
Section: Introductionmentioning
confidence: 99%
“…Ozgen and Duruk [9] showed that when the slow cooling process is applied continuously, not gradually, the systems firstly have a tendency of complex arrangement in cluster level at the glassy transition temperature, and, again, it returned to liquid state since they have an energetically unfavorable structure. Sarkar et al revealed that the induced pressure during solidification takes the aluminum in crystalline form even in very high cooling rate [10]. However, the atomic mechanism of crystallization from liquid metal has not yet been fully investigated.…”
Section: Introductionmentioning
confidence: 99%